Low genetic diversity and lack of genetic structure in the giant jellyfish Nemopilema nomurai in Chinese coastal waters. Issue 7 (8th August 2016) - Dong, Zhijun; Liu, Zhongyuan; Liu, Dongyan; Liu, Qingqing; Sun, Tingting
ABSTRACT: The giant jellyfish Nemopilema nomurai is a scyphozoan species well-known in East Asian Marginal Seas for its damage to fisheries. The genetic diversity and population structure of N. nomurai, collected from five geographic regions in Chinese coastal seas, were examined based on mitochondrial cytochrome c oxidase subunit I (COI) gene and nuclear internal transcribed spacer one (ITS1) sequences. A total of 26 and five unique haplotypes were recovered from the COI and ITS1 genes, respectively. The overall genetic diversity of N. nomurai calculated by the COI and ITS1 sequences was low (haplotype diversity 0.727% and 0.108%, nucleotide diversity 0.212% and 0.039%). The median-joining network analysis revealed a star-like haplotype network. The hierarchical Analysis of Molecular Variance (AMOVA) of COI haplotypes showed that N. nomurai populations form a single population, with a low FST (0.0149, p = 0.1036). The dispersal ability, together with the biological characteristics, could be important factors for the lack of a geographically structured pattern in N. nomurai in Chinese coastal waters.